Localisation of Damage in Private International Law - Boskovic, Olivera, (International Law E-Books Online, Collection 2025., 2024)
Localisation in private international law of torts is a notoriously difficult question. How do you localize financial or moral damage? What about latent damage? Should damage in the context of cyber-torts be localized differently? The great variety of tortious actions gives rise to endless difficulties ranging from banal situations involving material damage to climate change. Trying to find suitable solutions requires answering many difficult questions, such as the very definition of damage within the meaning of private international law rules, the influence of various considerations such as foreseeability, protection of the claimant, and the remedy sought. The contributions in this volume address these questions and more from the perspectives of 17 different countries, from Austria to Venezuela.